Complete DNA sequence coding for the large ribosomal RNA of yeast mitochondria. - Sor, F (1983)
The mitochondrial gene coding for the large ribosomal RNA (21S) has been isolated from a rho- clone of Saccharomyces cerevisiae. A DNA segment of about 5500 base pairs has been sequenced which included the totality of the sequence coding for the mature ribosomal RNA and the intron. The mature RNA sequence corresponds to a length of 3273 nucleotides. Despite the very low guanine-cytosine content (20.5%), many stretches of sequence are homologous to the corresponding Escherichia coli 23S ribosomal RNA. The sequence can be folded into a secondary structure according to the general models for prokaryotic and eukaryotic large ribosomal RNAs. Like the E.coli gene, the mitochondrial gene contains the sequences that look like the eukaryotic 5.8S and the chloroplastic 4.5S ribosomal RNAs. The 5' and 3' end regions show a complementarity over fourteen nucleotides.